(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
The present essay searches to connect philosophy, art, and communication, understanding social medias as platforms that support actual perceptions about image, especially self-image, popularly selfie. For this, we performed a bibliographic clipping in Walter Benjamin (1985) in dialogue with Didi-Huberman (2010) bringing thoughts about aura, cult, and image.